Comparative study of the mobility of Pd species in SSZ-13 and ZSM-5, and its implication for their activity as passive NOx adsorbers (PNAs) after hydro-thermal aging. Issue 1 (5th December 2018) - Lee, Jaeha; Ryou, YoungSeok; Hwang, Sungha; Kim, Yongwoo; Cho, Sung June; Lee, Hyokyoung; Kim, Chang Hwan; Kim, Do Heui
Abstract : PNA ability and hydrothermal stability of Pd/ZSM-5 and Pd/SSZ-13 catalysts were comparatively studied. Abstract : The comparative behavior of Pd species in ZSM-5 and SSZ-13 zeolite supports resulting from thermal treatment in the presence and absence of water was studied. Thermal treatment at 750 °C caused the atomic distribution of Pd species in ZSM-5, while clustered Pd species remained in SSZ-13. The addition of water in the feed during thermal treatment resulted in the Pd sintering in the Pd/ZSM-5 catalyst, although Pd dispersion and agglomeration were concurrently observed in the Pd/SSZ-13 catalyst, depending on the Pd loading. The prepared catalysts were vacuum-treated to induce the auto-reduction of the atomic Pd species, and to compare the mobility of the Pd species within the different zeolite frameworks. The isolated Pd species in ZSM-5 were completely reduced to form large Pd clusters after vacuum treatment, while most of the Pd species in SSZ-13 remained atomically dispersed, indicating that the Pd mobility is higher in the former than in the latter. Hence, the different behavior of Pd/ZSM-5 and Pd/SSZ-13 catalysts against the oxidative and hydrothermal treatments could be explained by the intrinsic difference in the Pd mobility within the different types of zeolite. It is likely that the smaller pore size of SSZ-13 than ZSM-5 contributed to the lesser Pd mobility in the former. The hydrothermal treatment deactivated the NO adsorption ability of the other prepared Pd/zeolite catalysts with larger pore openings (Beta and Modernite zeolites), which further supports the present proposal.